2022
DOI: 10.1007/s10067-022-06341-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of endothelial dysfunction in immunoglobulin-resistant children with acute Kawasaki disease

Abstract: Purpose Clinically, some children with Kawasaki disease (KD) who do not respond to the rst application of gamma globulin therapy have a longer course of disease and a higher risk of coronary artery damage. The characteristics of vascular endothelial dysfunction in intravenous immune globulin (IVIG)-resistant patients during the acute phase are not well described. We aimed to determine whether indicators that detect the situation of the endothelium are useful parameters that can accurately re ect subclinical dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The results confirm the existence of a process leading from acute and chronic inflammation to vascular endothelial dysfunction in humans, as shown in patients with Helicobacter pylori infection, patients with periodontal disease, patients with Kawasaki disease, patients with Bürger’s disease, and other inflammatory diseases [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Vascular endothelial function may be considered a marker of vascular inflammation, although various chemical biomarkers exist for inflammation.…”
Section: Inflammationsupporting
confidence: 79%
See 2 more Smart Citations
“…The results confirm the existence of a process leading from acute and chronic inflammation to vascular endothelial dysfunction in humans, as shown in patients with Helicobacter pylori infection, patients with periodontal disease, patients with Kawasaki disease, patients with Bürger’s disease, and other inflammatory diseases [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Vascular endothelial function may be considered a marker of vascular inflammation, although various chemical biomarkers exist for inflammation.…”
Section: Inflammationsupporting
confidence: 79%
“…Inhibition of NF-kB activity suppresses interlukin-6 (IL-6), VCAM-1 and MCP-1 expression [ 89 ]. Many studies have shown that inflammation may play a role in vascular injury [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. The presence of angiotensin II, oxidized LDL, and inflammatory cytokines activates NADPH oxidase, which in turn induces inflammation under the condition of oxidative stress due to excess ROS.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation